Indian women’s settlement experiences and the impact on their health: a narrative study in Brampton, Ontario - David Shiyokha Busolo; Sarah Ruth Kipp (BMJ Public Health)
Introduction Women who have immigrated from India experience health decline during settlement in Canada. However, little is known about how their settlement experiences impact their health. Accordingly, our study examined the impact of Indian women’s settlement experiences on their health.Method Eight Indian women aged 25–45 years were recruited for our study through purposive and snowball sampling. Guided by narrative inquiry, data collection included individual interviews and a demographic survey. Subsequently, data analysis was completed using Clandinin and Connelly’s thematic and holistic method.Results Narratives described three phases of settlement: ‘discovering and seeking’, ‘compromising and surviving’ and ‘transitioning and accepting’. Narratives of ‘discovering and seeking’ described the women’s process of exploring and learning about their surroundings and their efforts to obtain information and essential resources. Narratives of ‘compromising and surviving’ described how the women accepted circumstances below their expectations and applied extraordinary efforts to settle. Narratives of ‘transitioning and accepting’ depicted women becoming familiar, skilled and supported. This process led to them accepting their new lives and developing hope for a better future. Throughout these phases, women faced social determinants of health (SDOH) challenges and a lack of support which contributed to a decline in their health.Conclusion Challenges faced during settlement negatively impacted health. When SDOH challenges and distress persist, functional impairment, increased healthcare costs, chronic disease and mortality risk are likely. Alternatively, improved navigation support, culturally appropriate healthcare and equitable employment opportunities could promote Indian women’s health during settlement.